2010
DOI: 10.1007/s10461-010-9775-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV Disclosure, Condom Use, and Awareness of HIV Infection Among HIV-Positive, Heterosexual Drug Injectors in St. Petersburg, Russian Federation

Abstract: We examined the prevalence of HIV disclosure to sexual partners by HIV-positive drug injectors (IDUs) in St. Petersburg, Russia and compared the magnitude and direction of associations of condom use with awareness of one’s HIV infection and disclosure to partners. Among 157 HIV-infected participants, awareness of infection at time of last intercourse was associated with condom use with partners perceived to be HIV-negative (aOR 6.68, 95% CI 1.60–27.88). Among the 70 participants aware of their infection prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
3
17
1
Order By: Relevance
“…Our data agree with the findings of Amirkhanian et al 11 and Grau et al, 15 who found a 50% self-reported condom use among HIV-infected people, and is higher than that reported by Benotsch, 18 who found a 21% self-reported condom use among patients presenting at an STI clinic in St Petersburg. Multivariate analysis revealed that persistent condom use was negatively associated with serostatus disclosure, consistent with other studies.…”
Section: Condom Usesupporting
confidence: 92%
See 1 more Smart Citation
“…Our data agree with the findings of Amirkhanian et al 11 and Grau et al, 15 who found a 50% self-reported condom use among HIV-infected people, and is higher than that reported by Benotsch, 18 who found a 21% self-reported condom use among patients presenting at an STI clinic in St Petersburg. Multivariate analysis revealed that persistent condom use was negatively associated with serostatus disclosure, consistent with other studies.…”
Section: Condom Usesupporting
confidence: 92%
“…Multivariate analysis revealed that persistent condom use was negatively associated with serostatus disclosure, consistent with other studies. 15,19 Grau et al 15 reported a negative correlation between condom use and intercourse with a primary sexual partner, and a positive correlation between condom use and perceived seronegativity of the sexual partner. In our study, those reporting always wearing a condom were half as likely to have disclosed to their sexual partner.…”
Section: Condom Usementioning
confidence: 99%
“…HIV testing remains sub-optimal among PWIDs in Russia (Grau et al, 2011). Less than half of people living with HIV (PLHIV) in Russia have been diagnosed with HIV and 23% of those diagnosed are not linked to care (Pokrovskaya et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Only half of participants in an HIV-positive IDU sample from Russia used condoms at their last intercourse regardless of their partners’ serostatus. 74 Two other Russian survey studies among PLH, one conducted in 2002 72 and another in 2009, 73 found high rates of unprotected sex by persons aware of their positive HIV status. Most PLH had sexual partners of seronegative or unknown status, with a mean of 5.8 partners.…”
Section: Condom Use Among At-risk Populationsmentioning
confidence: 99%
“…Only three studies—one from Zagreb, Croatia 71 and three from St. Petersburg, Russia 7274 —have systematically recruited cross-sectional PLH samples from AIDS service provider settings. With respect to transmission risk behaviors, 20% of Croatian HIV-positive MSM reported unprotected intercourse with seronegative or status-unknown partners in the past 6 months, and half of them reported unprotected intercourse with multiple casual partners of unknown status.…”
Section: Condom Use Among At-risk Populationsmentioning
confidence: 99%